Criminal intelligence - Polikarpov, Vladimir A.; Aleshkevich, Sergey I. (Journal of the Belarusian State University. Sociology, 2019)
A new concept of criminal intelligence is introduced. Its nominal and ostensive definitions are given. The possibilities of its evaluation in terms of psychometrics are considered. The results of an empirical study conducted on the basis of one of the correctional institutions, as well as the analysis and interpretation of the results are presented. The use of neural network forecasting methods in the study of criminal intelligence is described.